Utilization of Bamboo fibre and M-sand in Concrete as a Replacement of Natural Sand - Mahendra Pratap Singh; Dharmendra Prajapati; Anudeep Nema (International Journal of Scientific Research in Civil Engineering, 2022)
In the current world, concrete has become a very important part of the construction industry and the materials which are used in making concrete have evolved due to better quality of cement and better grade of coarse aggregates. The sand is an important part of concrete. It is mainly procured from natural sources. Thus the grade of sand is not under our control. The concrete cubes of M-25 grade were threw in this trial explore work and tried to analyze different properties of concrete like compressive quality, workability. In this study M-sand is considered as a replacement of natural sand by 50, 70 & 90% by weight of sand in concrete design mix with 5% Bamboo fiber streams as an admixture. This study is carried out at the age of 7, 14, 21 and 28 days. In this work, the general properties of fresh and hardened concrete were tried and the outcomes were dissected. As concrete is a central material for the construction industry. In this study it is observed that M-sand in significantly increased the compressive of concrete with maximum strengths. Bamboo fiber helps in improving concrete properties to avoid cracks and failure.